2022
DOI: 10.1021/acsomega.2c01875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Radiation Sources on the Performance of Collagen-Based Corneal Repair Materials and Macrophage Polarization

Abstract: Owing to the lack of donor corneas, there is an urgent need for suitable corneal substitutes. As the main component of the corneal stroma, collagen has great advantages as a corneal repair material. If there are microorganisms such as bacteria in the corneal repair material, it may induce postoperative infection, causing the failure of corneal transplantation. Therefore, irradiation, as a common sterilization method, is often used to control the microorganisms in the material. However, it has not been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The breakage of the chemical bond of collagen in the cornea leads to a decrease in the tensile strength and strain‐at‐break and affects its applications as the decellularized extracellular matrix 19 . It had also been reported that different doses of electron beam irradiation could change the physical and chemical properties of biomaterials, such as swelling, tensile strength, and transmittance 20–22 . Thus, it is important to research the influences of the E‐beam radiation dose on the structure and biological properties of the APC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breakage of the chemical bond of collagen in the cornea leads to a decrease in the tensile strength and strain‐at‐break and affects its applications as the decellularized extracellular matrix 19 . It had also been reported that different doses of electron beam irradiation could change the physical and chemical properties of biomaterials, such as swelling, tensile strength, and transmittance 20–22 . Thus, it is important to research the influences of the E‐beam radiation dose on the structure and biological properties of the APC.…”
Section: Introductionmentioning
confidence: 99%
“…19 It had also been reported that different doses of electron beam irradiation could change the physical and chemical properties of biomaterials, such as swelling, tensile strength, and transmittance. [20][21][22] Thus, it is important to research the influences of the E-beam radiation dose on the structure and biological properties of the APC.…”
mentioning
confidence: 99%
“…have been developed and utilized to treat corneal blindness. Among those natural polymers, collagen has been extensively studied as the preferred material for corneal repair, because it possesses suitable physicochemical properties and biological characteristics similar to the native cornea [9]. At present, several collagen-based material has been reported to have achieve some specific functions, such as good biocompatibility [10], antibacterial effect (when adequate antimicrobial is incorporated) [11] and moisturizing performance [12].…”
Section: Introductionmentioning
confidence: 99%